AutoCAD 2012 and AutoCAD LT 2012 : no experience required - Gladfelter, Donnie, 1982-; Gladfelter, Donnie (Indianapolis, Indiana : Sybex, 2011)
"The perfect step-by-step introduction to Autodesk's powerful architectural design softwareWith this essential guide, you'll learn how to plan, develop, document, and present a complete AutoCAD project by building a summer cabin from start to finish. You can follow each step sequentially or jump in at any point by downloading the drawing files from the book's companion web site. You'll also master all essential AutoCAD features, get a thorough grounding in the basics, learn the very latest industry standards and techniques, and quickly become productive with AutoCAD 2012. Features concise explanations, focused examples, and step-by-step instructions for learning AutoCAD and AutoCAD LT in a hands-on project that runs throughout the book Addresses the newest features of AutoCAD 2012 and AutoCAD LT 2012 as well as emerging techniques and standards in the industry Begins with the basics such as the AutoCAD interface, basic commands, and creating drawings and gradually progresses to more advanced topics, including grouping, elevations, hatches, and using text in drawings Introduces dimensioning, external references, layouts and printing, and using 3D AutoCAD and AutoCAD LT: No Experience Required helps you quickly learn to use AutoCAD and AutoCAD LT right away"
Chapter 1 Get ting to Know AutoCAD. -- Chapter 2 Learning Basic Commands to Get Started. -- Chapter 3 Set ting Up a Drawing. -- Chapter 4 Developing Drawing Strategies: Part 1. -- Chapter 5 Developing Drawing Strategies: Part 2. -- Chapter 6 Using Layers to Organize Your Drawing. -- Chapter 7 Combining Objects into Blocks. -- Chapter 8 Controlling Text in a Drawing. -- Chapter 9 Using Dynamic Blocks and Tables. -- Chapter 10 Generating Elevations. -- Chapter 11 Working with Hatches, Gradients, and Tool Palettes. -- Chapter 12 Dimensioning a Drawing. -- Chapter 13 Managing External References. -- Chapter 14 Using Layouts to Set Up a Print. -- Chapter 15 Printing an AutoCAD Drawing. -- Chapter 16 Creating 3D Geometry. -- Chapter 17 Rendering and Materials
Includes index.
Keywords: AUTOCAD